"Scheiden tut weh" - Kommunikationsstörungen zwischen Fachleuten und Laien im Ehescheidungsrecht - Eckardt, Birgit (HERMES - Journal of Language and Communication in Business, 2002)
Like any other science, the jurisprudence uses a cant, that is not self –explanatory for the layman. It is even more difficult, that in certain legal fields laymen are not only the affected ones, but also the agents, who require the secular intermediation of a solicitor. Thereby occurring communication problems are attributed to the large terminology. It will be shown by means of a four step communication model while using the example of the divorce legislation, why and on what communication levels the commu-nication between experts and laymen is disturbed. The interdisciplinary research approach, that considers linguistic and jurisprudential as well as psychological and sociological aspects, shows the rather unexpected report, that communication perturbations between solicitors and clients occur to the same extent on the content level as on the relationship level. Objective misunderstandings are easier to remove than problems on the relationship level. Communication problems between judges and parties occur mainly during the very formalised (written) proceedings because of factual ignorance. The oral proceedings take place mainly undisturbed, when judges and solicitors measure up their role as mediator, respectively conciliator.